2002
DOI: 10.1007/s00424-001-0760-2
|View full text |Cite
|
Sign up to set email alerts
|

pH gating of lens fibre connexins

Abstract: Chemical gating of gap junction channels by intracellular pH may be an important mechanism for the physiological regulation of cell-cell coupling. In the ocular lens, pH gating of gap junction channels has been implicated as a possible cause of cataract in diabetics. To address this question further, I determined the pH dependence of the rat connexin (Cx)-46 and ovine Cx49 in transfected HeLa cells using the pH-clamp technique during dual whole-cell recording. pH gating for both connexins was fast and reversib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…This may not come as a surprise when one considers that the lowest pH of 6.5 detected in the nucleus [20], [72] is not too different from the neutral pH of 7.0 explored by our study, which also induces amorphous aggregation in HγD-crys. While our experimental condition is an over simplified model of what’s going on in the lens, it is undeniable that the inherent aggregation property of HγD-crys under neutral pH is of the amorphous kind.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…This may not come as a surprise when one considers that the lowest pH of 6.5 detected in the nucleus [20], [72] is not too different from the neutral pH of 7.0 explored by our study, which also induces amorphous aggregation in HγD-crys. While our experimental condition is an over simplified model of what’s going on in the lens, it is undeniable that the inherent aggregation property of HγD-crys under neutral pH is of the amorphous kind.…”
Section: Discussionmentioning
confidence: 42%
“…One involves the possibility of partially degraded HγD-crys forming fibrillar aggregates in the low pH environment of lysozomal compartment during lens fiber cell differentiation, which may be involved in the early stages of cataract formation [18]. Another hypothesis has to do with the decreased pH in the lens nucleus overtime leading to loss of α-crystallin chaperone capability to protect HγD-crys from aggregation, thus resulting in senile nuclear cataract formation [20], [21]. Regardless of the mechanisms of cataract formation, the only accepted form of treatment currently available is the surgical removal of the opaque lens and replacement with an artificial lens.…”
Section: Introductionmentioning
confidence: 99%
“…Gap junctions composed of Cx46 and/or Cx50 contribute to intercellular coupling in differentiating lens fibers, while only Cx46 channels are functional in mature fibers (2,19,21,37,65). In DKO lenses, we observed a ϳ50% decrease in conductance in DKO lens fibers compared with the control.…”
Section: Discussionmentioning
confidence: 54%
“…DeRosa et al (47) showed COOH termini cleaved Cx50 channels, when exogenously expressed in oocytes, went to the plasma membrane and formed plaques, but the constituent channels were rarely open. Exogenous expression of COOH termini cleaved Cx46 channels showed no differences in coupling from expression of intact protein (60). Putting all of these results together suggests the following hypothesis: Cx46 and Cx50 form mostly homomeric channels in the plaques coupling the DF, where each contributes about equally to coupling conductance.…”
Section: Roles Of Connexin46 and Connexin50 In Fiber Cell Couplingmentioning
confidence: 99%